"Resnica" o deklicah? - Vendramin, Valerija (Šolsko polje, 2006)
The author first presents some of the problems related to the research of different "representations" of sexual difference in school (e.g. the differences in achievement of boys and girls, subtle discrimination, etc.). She problematizes some aspects of quantitative research in this area, which donot allow for more complex analyses of feminine and masculine. By briefly presenting feminist reseach paradigm she sheds some light on the question of "objectivity". She then presents some typical assumptions about "natural" abilities of boys and girls. At the end, she analyses the concept of hidden curriculum, which opens additional possibilities in gender research in education beyond "common sense" and "scientific proof".
Keywords: spolne razlike; prikriti kurikulum; učenje; learning; učna uspešnost; metodologija